Formowanie się księgozbiorów i bibliotek dla dzieci w II połowie XIX i początku XX wieku na przykładzie Łodzi - Konieczna , Jadwiga (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The aim of this dissertation was to present the trends and forms of development of information about books and literature for children in 19th and the beginning of 20th century on Polish territory. The author took into consideration different conditions: pedagogical, cultural and socio-political. Throughout the whole period magazines publishing book reviews and bibliographic specifications and also publishing houses and booksellers with their announcements and advertisements played a significant role in creation of the information about books for children. As the years went on and with the development of publishing market the system of information was extended by different sorts of folders, publishers’ and bookshops’ catalogues and printed librarian catalogues. On the turn of the centuries reference catalogues (of a hand-book character) became popular. Their aim was to shape the reading habit among children and youth.